(untitled) (Open International Journal of Informatics, 2021)
Malaysia’s healthcare industry has historically been slow to embrace health information technology. By enhancing the efficiency of electronic health records, blockchain technology can help eliminate medical errors and data breaches while also facilitating the exchange of health information. Before deploying blockchain, building a conceptual framework for assessing health professionals’ readiness as the primary user can aid policymakers in planning technology and strategy development. In comparison to the number of studies on the acceptability of health technology, there is a shortage of research on the adoption of blockchain technology. A readiness assessment framework is currently absent from the blackchin-based health information technology literature. The current study explores the factors influencing health professionals’ willingness to embrace blockchain technology in Malaysian public hospitals to overcome this gap. Additionally, this study develops a conceptual model that combines the Unified Theory of Acceptance and Use of Technology (UTAUT), the Norm Activation Model (NAM), and initial mediator trust. The suggested conceptual framework will be practically evaluated and validated in the future.